Providing care for children with low vision - Karin van Dijk (Community Eye Health Journal, 2007)
The importance of providing care for children with low vision is recognised by many initiatives, such as VISION 2020, the 2004 Oslo Workshop on Low Vision,1 and the United Nation's global campaign, Education for All.